Exploring water consumption in Dhaka city using instrumental variables regression approaches - Siddiquee, Muhammad Shahadat Hossain; Ahamed, Raihan (Springer Link, 2022)
This article was published in Environmental Processes [©2012 Published by Oxford Journal] and the definite version is available at: http://doi.org/10.1093/heapol/czr059 The Article's website is at: http://heapol.oxfordjournals.org/content/27/6/477